Doxastic spaces: a new approach to relational beliefs and unstable neglect - Rook, D (2015)
This thesis introduces and explores a novel construct for studying human beliefs in social science: doxastic spaces. These flexible analytical devices are demonstrated as capturing three key properties of beliefs which are difficult to depict through other formats: the relational, relative, and reflexive properties of beliefs. The doxastic-space paradigm developed by this thesis is likewise shown to enable new and insightful theories about belief formation and change. Two such theories cultivated herein are quantized evidence theory (QET) and entropy-based social learning (EBSL). These theories prioritise not only the evidential bases of beliefs, but also the cognitive limitations on memory and attention that people face in constructing and updating beliefs about their worlds. Such bases and limitations underscore not only the role that context has to play in sculpting beliefs, but also the reciprocal function of beliefs in helping to determine and demarcate context. Part of that context is discussed as being other people relevant in social judgment and learning situations. And interplay between beliefs and context is used to aid explanation for unstable tendencies in neglectful cognition. The work mixes theoretical and empirical investigation of the doxastic-space framework, and suggests that it may serve social science by working to not only forge deeper comprehension of belief dynamics but also to operate as a platform for interdisciplinary exchange.